Attitude of senior secondary school students toward e-learning - Nasrin; Biswas, Komy (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
E-learning is one of the influential instructional education programmes that help students to their studies. The main aim of this investigation is to determine the attitude of senior secondary school students towards e-learning. Quantitative research method was used to conduct the study. Data were collected from 78 students by using simple random sampling technique. Sample data were collected through an Attitude scale developed and standardized by Dimpal Rani. Mean, SD, t-test and correlation coefficient were used to analysed and interpret the data. Results showed that students had low level attitude towards e-learning and gender had no effect on attitudes of senior secondary students towards e-learning and its components. The study outcome also indicated that there was a positive correlation between different factors of e learning. The results of the study were discussed in relation to the relevant literature, and some suggestions were made.